The Impact of Trimethylamine N-Oxide on Atrial Fibrillation Presence in Patients with Cardiovascular Disease - Cristian Marius Florea; Radu Ovidiu Rosu; Ioan Alexandru Minciuna; Gabriel Cismaru; Dana Pop; Ana-Maria Vlase; Iuliana Nenu; Gabriela Adriana Filip (Journal of Xenobiotics)
Background: Atrial fibrillation is the most common human heart rhythm disorder, yet its underlying causes remain largely unknown. Trimethylamine N-oxide (TMAO), a by-product derived from the gut microbiota contributed by red meat, has been linked to numerous cardiovascular and metabolic diseases. Aims: This study aimed to evaluate the impact of serum TMAO levels on the occurrence of atrial fibrillation in patients with cardiovascular disease. Results: Utilizing a cross-sectional study design, fasting serum TMAO levels were measured and compared between 153 patients without cardiovascular disease and patients hospitalized for cardiovascular disease, stratified by the presence or absence of atrial fibrillation. While patients with more comorbidities had higher TMAO overall, the TMAO levels were not significantly different between cardiovascular disease patients with and without atrial fibrillation (p = 0.57). Moreover, there was no difference between atrial fibrillation progression phenotypes (p = 0.27). In multivariate analysis, a significant association was found with atherosclerotic cardiovascular disease (p = 0.04) and chronic kidney disease (p < 0.001), but there was no significant association between TMAO and atrial fibrillation (p = 0.9). Conclusions: Serum TMAO levels are not associated with the occurrence of atrial fibrillation and disease progression phenotypes in patients with cardiovascular disease, but are associated with ASCVD and CKD.